Internal quality control – past, present and future trends - Ricós Carmen; Fernandez-Calle Pilar; Perich Carmen; Westgard James O. (Advances in Laboratory Medicine, 2022)
This paper offers an historical view, through a summary of the internal quality control (IQC) models used from second half of twentyth century to those performed today and wants to give a projection on how the future should be addressed.